Extracellular biosynthesis of Cu2-xSe nanocrystallites with photocatalytic activity. (March 2019) - Qi, Shiyue; Yang, Shuhui; Yue, Lei; Wang, Jia; Liang, Xinrui; Xin, Baoping
Graphical abstract: Highlights: Cu2-x Se nanospheres (NSs) were for the first time biosynthesized by P. agglomerans . The biogenic Cu2-x Se NSs were uniform (∼80 nm in diameter) and crystalline. The crystalline Cu2-x Se NSs had a face-centered cubic structure. Extracellular proteins capping the Cu2-x Se NSs had molecular masses 25–110 kDa. The Cu2-x Se NSs showed a good photocatalytic activity in methylene blue degradation. Abstract: Semiconductor Cu2-x Se nanospheres were successfully biosynthesized based on bioreduction of SeO3 2− into Se 2- by the selenite-reducing bacterium, Pantoea agglomerans . The Cu2-x Se nanospheres had excellent crystallinity with a face-centered cubic structure and an average diameter of 80 nm. Composition and oxidation states analysis using X-ray photoelectron spectroscopy and X-ray energy dispersive spectroscopy followed by optical characterization using ultraviolet-visible and Fourier transform infra-red spectroscopy confirmed that the biosynthesized Cu2-x Se nanospheres were capped by proteins. The extracellular proteins which mediated biosynthesis were visualized by excitation–emission matrix fluorescence spectroscopy. Sodium dodecyl sulfate-polyacrylamide gel electrophoretic analysis revealed that the molecular masses of proteins were about 110, 50, 38, 35 and 25 kDa. The biosynthesized Cu2−x Se nanospheres showed an excellent and stable photocatalytical activity under sunlight irradiation in the degradation of methylene blue for four cycles. This study put forward a green and toilless way to manufacture copper selenide nanoparticles using a biological process.